Activity of enzalutamide in men with metastatic castration resistant prostate cancer is affected by prior treatment with abiraterone and/or docetaxel - Cheng, Heather H. (Prostate Cancer Prostatic Dis, 2015)
BACKGROUND: Enzalutamide and abiraterone are new androgen-axis disrupting treatments for metastatic castration resistant prostate cancer (mCRPC). We examined response and outcomes of enzalutamide-treated mCRPC patients in the real-world context of prior treatments of abiraterone and/or docetaxel. METHODS: We conducted a seven-institution retrospective study of mCRPC patients treated with enzalutamide between January 2009 and February 2014. We compared baseline characteristics, PSA declines, PSA progression-free survival (PSA-PFS), duration on enzalutamide, and overall survival (OS) across subgroups defined by prior abiraterone and/or docetaxel. RESULTS: Of 310 patients who received enzalutamide, 36 (12%) received neither prior abiraterone nor prior docetaxel, 79 (25%) received prior abiraterone, 30 (10%) received prior docetaxel, and 165 (53%) received both prior abiraterone and prior docetaxel. Within these groups, respectively, ≥30% PSA decline was achieved among 67%, 28%, 43%, and 24% of patients; PSA-PFS was 5.5 (95% CI 4.2–9.1), 4.0 (3.2–4.8), 4.1 (2.9–5.4), and 2.8 (2.5–3.2) months; median duration of enzalutamide was 9.1 (7.3-not reached), 4.7 (3.7–7.7), 5.4 (3.8–8.4), and 3.9 (3.0–4.6) months. Median OS was reached only for patients who received both prior abiraterone and docetaxel and was 12.2 months (95% CI 10.7–16.5). 12-month OS was 78% (59%–100%), 64% (45%–90%), 77% (61%–97%), and 51% (41%–62%). Of 70 patients who failed to achieve any PSA decline on prior abiraterone, 19 (27%) achieved ≥30% PSA decline with subsequent enzalutamide. CONCLUSIONS: The activity of enzalutamide is blunted after abiraterone, after docetaxel, and still more after both, suggesting subsets of overlapping and distinct mechanisms of resistance.